Absorb bioresorbable scaffold versus Xience metallic stent for prevention of restenosis following percutaneous coronary intervention in patients at high risk of restenosis: Rationale and design of the COMPARE ABSORB trial - Chang, Chun Chin; Onuma, Yoshinobu; Achenbach, Stephan; Barbato, Emanuele; Chevalier, Bernard; Cook, Stéphane; Dudek, Dariusz; Escaned, Javier; Gori, Tommaso; Kočka, Viktor; Tarantini, Giuseppe; West, Nick E.J.; et al. (Cardiovascular Revascularization Medicine, 2019)
Background: The advent of bioresorbable vascular scaffolds (BVS)was considered as a potential improvement in percutaneous coronary intervention (PCI)after the groundbreaking development of drug eluting stents (DES). However, the clinical performance, long-term safety and efficacy of BVS in complex coronary lesions remain uncertain. COMPARE ABSORB, a multicenter, single blind, prospective randomized trial, aims to compare the clinical outcomes between the Absorb BVS and Xience everolimus-eluting metallic stent (EES)in patients with coronary artery disease and a high risk of restenosis. Design: COMPARE ABSORB is designed to enroll 2100 patients at up to 45 European sites. Enrolled patients will possess high risk for restenosis due to clinical profile or coronary lesion complexity and will undergo elective or emergent PCI. Once included in the study, patients will receive either Absorb BVS or Xience EES. Specific advice on implantation technique including mandatory pre-dilatation, sizing and post-dilatation (PSP), will be used in the Absorb BVS arm. The primary endpoint is target lesion failure (TLF), a device-oriented composite endpoint (cardiac death, target vessel myocardial infarction and clinically-indicated target lesion revascularization). The trial is powered to assess non-inferiority of Absorb BVS compared with Xience EES with a predetermined non-inferiority margin of 4.5% at 1 year after index procedure. The clinical follow-up will continue for 7 years. Conclusions: The prospective COMPARE ABSORB randomized trial (ClinicalTrials.gov NCT02486068)will help to assess the long-term safety and efficacy of Absorb BVS compared with Xience EES in the treatments of patients with complex coronary artery disease and a high attendant risk of restenosis.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Absorb; Bioresorbable scaffold; Coronary artery disease